2000
DOI: 10.1007/s11663-000-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium slag losses in ferrovanadium production

Abstract: Ferrovanadium is sometimes produced from V 2 O 3 in electric arc furnaces, using aluminum as a reductant. The CaO fluxes the alumina, which forms during reduction of the vanadium oxide. Incomplete reduction of vanadium oxide from the slag is a significant cause of vanadium losses. To quantify factors that can affect the equilibrium vanadium loss, the vanadium oxide activity coefficient was measured experimentally for different slag compositions. Hydrogen-water mixtures were used to control the partial oxygen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 2 publications
1
18
0
Order By: Relevance
“…Vermaak and Pistorius reported that slag basicity affects the amount of dissolved vanadium in the oxide phases. Figure shows EDS analysis results of vanadium distribution in equilibrium phases in samples treated in air.…”
Section: Discussionmentioning
confidence: 99%
“…Vermaak and Pistorius reported that slag basicity affects the amount of dissolved vanadium in the oxide phases. Figure shows EDS analysis results of vanadium distribution in equilibrium phases in samples treated in air.…”
Section: Discussionmentioning
confidence: 99%
“…The dissolved vanadium oxide content of slags has been reported by Vermaak and Pistorius (2000). Their 4 Iron-vanadium phase diagram (Massalski, 1986) Vermaak (2000) also examined the metallic droplet content of industrial ferrovanadium slags.…”
Section: Aluminothermic Smelting Of Vanadium Oxidesmentioning
confidence: 99%
“…Windimurra operators do not measure the temperature during smelting but believe that it mostly lies between 1850uC and 1900uC. Vermaak and Pistorius (2000) give a tapping temperature for the unnamed South African smelter of 1840uC. A temperature of 1850uC will be assumed for the modelling.…”
Section: Temperaturementioning
confidence: 99%
“…Tian et al measured the activity of VO in the CaO–SiO 2 –VO melts at 1773 K under the oxygen partial pressure of approximately 10 −16 atm. Vermaak et al measured the activity of V 2 O 3 in the CaO–Al 2 O 3 –V 2 O 3 system at 1973 K under the oxygen partial pressure of approximately 10 −13 atm. In these studies, only the effect of the composition on the activity of vanadium oxide was considered.…”
Section: Introductionmentioning
confidence: 99%